THE DIVERSITY AND RICHNESS OF TREE SPECIES OF TAMBANG SAWAH FOREST, KERINCI-SEBLAT NATIONAL PARK, SUMATRA INDONESIA - Agus Susatya (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
The conservation of tropical ecosystem is increasingly relevant as the recent global warming and climate change generate serious impacts on human life. Tropical forest becomes an important ecosystem to fight global warming due to its capability to sequester atmospheric carbon and to mitigate climate change. It is very unfortunate that such a vital ecosystem has been severely subjected to conversion to both plantations and illegal loggings. The tropical ecosystem has long been recognized to have high species diversity, but very few individual trees per species. The latter is almost ignored, even though can certainly bring serious difficulties on tree conservation. The objectives of the research were to know the tree community structure of Tambang Sawah Forest, Kerinci-Seblat National Park, and to determine the rareness of tree species. A plot of 1 ha was established at Tambang Sawah, Kerinci-Seblat National Park, Lebong Regency. All trees with BDH of > 5 cm were collected their herbarium specimens, and identified. The results showed that Tambang Sawah forest consists of 42 families, 94 genera, and 185 tree species/ha. It has 19.51% (8 families), and 26.82% (10 families) respectively categorized as very rare and rare. The pattern also occurs at genus level, where both categories contribute to 81.91% (78 genera) of the total genera. In species level, both are respectively 90 and 28 species, and altogether contribute to 63.78% of the total species. These values appeared higher than that of the other forests in Bengkulu. Across taxon level, very rare and rare categories appeared to be an ecological attribute in Sumatran forests. This implies that the loss of single tree can cause the loss of entire family. The conservation works even turn into more difficult, because tropical trees are commonly diocious, even bisexual trees, they tend to be self-incompatible, and out-crossed, and required at least 200 mature trees to ensure sexual regeneration and to avoid species extinction.